Addressing stunting in Karangwangi: Optimal strategies for toddlers, adolescents, and pregnant women - Ihsani Tamia; Raden Ardra Catur Fauzan (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Stunting is a problem that requires more attention because it can have an impact on children's lives into adulthood, especially the risk of physical and cognitive developmental disorders if not appropriately handled. The service aims to educate the local community through collaboration between the Karangwangi Village PKK Movement Team, BKKBN, Karangwangi Village Health Center, and the Thematic KKN Team of Universitas Pendidikan Indonesia about the dangers of stunting and the importance of a clean and healthy lifestyle (PHBS). The community services were conducted based on the program that had been implemented on July 26-August 26, 2023 in Karangwangi Village through the methods of (a) direct discussion between students and TP-PKK for posyandu activities; (b) community education about stunting in the form of counseling, distributing printed media in the form of posters and brochures directly to counseling participants; (c) socialization to Karangsari Elementary School students regarding clean and healthy living behavior (PHBS); and (d) health checks in CEKAS activities, and POSBINDU-PTM. The results showed that Karangwangi Village is in a zero stunting condition; government programs and innovative activities support this, so it is expected to prevent and increase public understanding of the dangers of stunting in the Karangwangi Village community.   Abstrak Stunting menjadi permasalahan yang memerlukan perhatian lebih karena dapat berdampak bagi kehidupan anak hingga dewasa, terutama risiko gangguan perkembangan fisik dan kognitif apabila tidak segera ditangani dengan baik. Pengabdian yang dilakukan bertujuan untuk mengedukasi masyarakat setempat melalui kolaborasi antara Tim Penggerak PKK Desa Karangwangi, BKKBN, Puskesmas Desa Karangwangi, dan Tim KKN Tematik Universitas Pendidikan Indonesia mengenai bahaya stunting dan pentingnya pola hidup bersih dan sehat (PHBS). Pengabdian ini dilakukan berdasarkan program yang telah dilaksanakan pada 26 Juli - 26 Agustus 2023 di Desa Karangwangi melalui metode (a) diskusi secara langsung antara mahasiswa bersama pihak TP-PKK untuk kegiatan posyandu; (b) edukasi masyarakat mengenai stunting dalam bentuk penyuluhan, penyebaran media cetak berupa poster dan brosur secara langsung kepada peserta penyuluhan; (c) sosialisasi kepada siswa SD Karangsari mengenai perilaku hidup bersih dan sehat (PHBS); dan (d) pengecekan kesehatan dalam kegiatan CEKAS, dan POSBINDU-PTM. Hasil penelitian menunjukkan bahwa Desa Karangwangi berada dalam kondisi zero stunting, hal tersebut didukung oleh program pemerintah dan inovasi kegiatan yang ada, sehingga diharapkan dapat mencegah serta meningkatkan pemahaman masyarakat mengenai bahaya stunting di lingkungan masyarakat Desa Karangwangi. Kata Kunci: balita; ibu hamil; stunting; sosialisasi dan mentoring